Age-Associated Changes in Estrogen Receptor Ratios Correlate with Increased Female Susceptibility to Coxsackievirus B3-Induced Myocarditis - Koenig, Andreas; Buskiewicz, Iwona; Huber, Sally A. (Frontiers in Immunology, 2017)
Sexual bias is a hallmark in various diseases. This review evaluates sexual dimorphism in clinical and experimental coxsackievirus B3 (CVB3) myocarditis, and how sex bias in the experimental disease changes with increased age. Coxsackieviruses are major causes of viral myocarditis, an inflammation of the heart muscle which is more frequent and severe in men than women. Young male mice infected with CVB3 develop heart-specific autoimmunity and severe myocarditis. Females infected during estrus (high estradiol) develop T regulatory cells and when infected during diestrus (low estradiol) develop autoimmunity similar to males. During estrus, protection depends upon estrogen receptor alpha (ERα) which promotes type I interferon, activation of natural killer/natural killer T cells and suppressor cell responses. Estrogen receptor beta (ERβ) has opposing effects to ERα and supports pro-inflammatory immunity. However, the sexual dimorphism of the disease is significantly ameliorated in aged animals when old females become as susceptible as males. This correlates to a selective loss of the ERα which is required for immunosuppression. Therefore, sex-associated hormones control susceptibility in the virus mediated disease, but their impact can alter with the age and physiological stage of the individual.